Citizenship: from three to seven principles of belonging. (2nd January 2022) - Cohen, Robin
ABSTRACT: Conventionally, three 'laws' are said to govern the recognition of citizenship. These are the laws of descent, birthplace and marriage. I question whether these are laws at all, and suggest that they are more like mutable principles underlying state practices that have evolved considerably in the last few decades. In addition to these three changing principles, I suggest that there are four other principles governing citizenship and social belonging. These are the principles of empire, price, transnationalism and co-presence. All are explained and situated, with a focus on a number of contemporary examples.